PENGARUH GAYA KEPEMIMPINAN, SELF EFFICACY DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS TANAMAN PANGAN, HOLTIKULTURA DAN PETERNAKAN KABUPATEN KUTAI TIMUR - Salmah Lafina; Ausy Riana; Juwita Aprillia; Jainuddin (Program Studi Manajemen, 2025)
The Influence of Leadership Style, Self-Efficacy and Employee Commitment on Employee Performance at the Food Crops, Horticulture, and Animal Husbandry Service of East Kutai Regency. This study uses an explanatory survey method. The population is 164 ASN, using a sample of 103 respondents. The analysis tool uses SPSS. The results of the study 1. Leadership style does not significantly influence employee performance at the Food Crops, Horticulture, and Animal Husbandry Service of East Kutai Regency. This means that leadership style has a strong or real influence between the way a person leads and the level of employee performance, 2. Self-Efficacy has a significant effect on employee performance at the Food Crops, Horticulture, and Animal Husbandry Service of East Kutai Regency. This means that the greater the self-efficacy, the greater the employee performance, 3. Organizational commitment has a significant effect on employee performance at the Food Crops, Horticulture, and Animal Husbandry Service of East Kutai Regency. This means that the greater the organizational commitment, the greater the employee performance, 4. Leadership, self-efficacy and organizational commitment simultaneously have a significant effect on employee performance. This means that the greater the leadership, self-efficacy, and organizational commitment, the greater the employee performance.